Anti-CCP Antibody and Rheumatoid Factor among Clinically Diagnosed Rheumatoid Arthritis Patients Attending a Tertiary Hospital at Chitwan, Nepal - Mandal, Fuleshwar; KC, Dilip; Adhikari, Kishor (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Rheumatoid Arthritis (RA) is a common, chronic inflammatory multisystem autoimmune disorder of undetermined aetiology involving primarily the synovial membranes and articular structures of many joints. Rheumatoid factor (RF) is most frequently used serum biomarkers for the diagnosis of RA; however, these antibodies are detectable in many other pathological conditions and even in 5% in healthy population. Anti-Cyclic Citrullinated Peptide (Anti-CCP) antibodies is another serological biomarker having high sensitivity and specificity than RF which present in pre-clinical stage and seronegative rheumatoid arthritis patients. MATERIALS AND METHODS: This is a cross-sectional study conducted among the confirmed RA patients visiting orthopaedic OPD. Anti-CCP antibody was determined quantitively by CLIA on Siemen ADVIA Centaur CP immunoassay system and RA-factor were determined quantitively by Nephelometry assay on MISPA I3 and comparison was done between two serological tests, i.e., Anti-CCP and RF. RESULTS: Out of 112 clinically diagnosed RA patients, 23 (20.5%) were males and 89(79.5%) were females with the ratio of 1:3.9 and the mean age ± SD of the patients was 50 ± 14.56. Out of 112 clinically diagnosed RA patients, 55 patients, i.e., 49.1% were RF antibodies positive and 57 patients, i.e., 50.9% were RF antibodies negative. Among RF positive, 32 (58.2%) patients were positive for anti-CCP antibody and among RF negative, 10 (17.5%) patients were positive for anti-CCP antibody and the differences between Anti-CCP and RF groups was statistically highly significant (p<0.001). CONCLUSIONS: Females are at high risk of developing Rheumatoid arthritis than males because male to female ratio is found to be 1:3.9. This study also showed that Anti-CCP antibody is more beneficial and better marker than RF for the diagnosis of Rheumatoid arthritis.